Richness of poroid Agaricomycetes from Serra do Navio, eastern Amazonia, Brazil, with a new record of Oxyporus lacera for Brazil - Xavier, William Kalhy Silva; Sotão, Helen Maria Pontes; Soares, Adriene Mayra da Silva; Gibertoni, Tatiana Baptista; Rodrigues, Felipe de Jesus; Ryvarden, Leif (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2018)
This work presents the poroid Agaricomycetes found in forest areas of Serra do Navio, state of Amapá, in the Brazilian Amazon. Taxonomic study and morphological analyses of collected specimens resulted in the identification of 100 species of Agaricomycetes, distributed in 54 genera, ten families, and three orders (Hymenochaetales, Polyporales, and Russulales). All species represent the first records for the study area, and 18 are new records for the state of Amapá, four are new for the Brazilian Amazon and Oxyporus lacera Ryvarden is reported for the first time for Brazil. Taxonomic comments, geographic distributions, and illustrations of this species are provided herein. As for the relative frequency, about 79% of the species were considered rare, 20% were occasional, and only 1% were considered frequent. This study increases our knowledge of the geographic distribution of these species in the Brazilian Amazon.